Sn6[P12N24] – A Sodalite‐Type Nitridophosphate. Issue 3 (22nd December 2014) - Pucher, Florian J.; Frhr. von Schirnding, Constantin; Hummel, Franziska; Celinski, Vinicius R.; Schmedt auf der Günne, Jörn; Gerke, Birgit; Pöttgen, Rainer; Schnick, Wolfgang
Abstract: Sn6 [P12 N24 ] was synthesized from Sn and HPN2 at 820 °C in an evacuated silica glass ampoule. According to powder X‐ray diffraction investigations and Rietveld refinement [space group I $\bar {4}$ 3 m (no. 217), a = 8.2882(2) Å, RP = 0.03645, wRP = 0.04613], Sn6 [P12 N24 ] crystallizes with a sodalite‐type structure with a reduced occupation factor of 3/4 for the Sn atom at Wyckoff site 8 c and an empty Wyckoff site 2 a at the center of the β‐cages. The structural results are further corroborated by energy‐dispersive X‐ray spectroscopy (EDX) analyses, solid‐state NMR spectroscopy, and theoretical investigations (DFT), including density of states (DOS), energy/volume, and electron localization (ELF) calculations. The 119 Sn Mössbauer spectrum shows a single, quadrupole‐split signal for Sn II at an isomer shift of 3.05 mm/s. In addition to SiPN3 with a defective wurtzite type of structure, the nitridophosphate sodalite Sn6 [P12 N24 ] represents the second ternary nitridophosphate containing only p‐block elements. Abstract : The new pseudobinary nitridophosphate Sn6 [P12 N24 ] is synthesized and investigated. The β‐cage of this compound, which crystallizes with the sodalite type of structure, is partially empty, as shown by several experimental and theoretical methods.